Conspectus and differentiation of species diversity of Pyryatyn’s urban flora (Poltava region) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Despite intensive floristic and geobotanical research on the Dnipro Left Bank, there is a lack of information on the urban flora of medium and small cities. We conducted inventory of the sp ecies diversity of Pyriatyn flora and the patterns of its differentiation. The total list of vascular plants are included 933 species from 5 divisions on the studied territory. We provide information about occurrence in the territorial zones of the city a nd its coenoflora for each species. The high level of species diversity of urban flora is associated with the preservation of a part of the floodplain of the Uday River and protected areas, as well as a representative floral complex of synanthropic plants, which is enriched new elements due to trade and transport links. The high level of species diversity was fixed in the territorial zones of protected areas (723 species) and recreational use (704), while the areas of engineering infrastructure, utilities, production, special and historical and cultural purposes have low values of species diversity due to the total transformation of the environment. The distribution of coenofloras by level of species diversity indicates that the highest level of floristic ca pacity is inherent in meadow and fringe ceonoflora, and significant species diversity is concentrated in the settlements occupied by ruderal vegetation. Forest, shrub and steppe coenofloras have reduced species diversity due to high levels of anthropogenic pressure. Dendrogram of floristic similarity of coenoflora within Pyriatyn city, although quite dendrogram of floristic similarity of regional flora to which it belongs, still has a number of specific features, including close integration of ruderal and q uasi natural ceonofloras with coastal and floodplain forest as a result of apophyte penetration and alien species in natural ecosystems.
Keywords: anthropogenic transformation, biodiversity, territorial zones, coenoflora.